Experimental & numerical study on sheet metal lateral bending with fixed and pinned ends - Norazlianie, Sazali (2012)
The main objective of this project is to expose student with many aspect of engineering work, design, fabrication and testing a product. The task follows a common product development activity, where student need to apply all their engineering knowledge and skill to complete this project. In random, student must know some basic knowledge which is buckling definition, software and machine to be used also the finite element method. In the other hand, student must master in conceptual design and complete loose part for an assembly drawing. Not only that, student must know how to solve problem in fabrication work and can develop similar model on Finite Element software. From an engineering standpoint, the finite element method is a method for solving engineering problems such as stress analysis, heat transfer, fluid flow and electromagnetic by computer simulation. The flow of the experiment is to be done from beginning until the testing is conducted to the specimen to determine the output of the buckling test when the combination of the joint are fixed and pinned. These projects explain how the design looks like, how the test rig fabricates also failure and error during the test is going on. From this project, we can prove that the experimental result is same with the simulation result.